Peran kepribadian, persepsi risiko, dan bias optimisme terhadap perilaku pencegahan penularan COVID-19 - Abu Bakar Fahmi (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2023)
The Coronavirus Disease (Covid-19) pandemic affects various aspects of people's lives around the world, including in Indonesia. The Covid-19 vaccines are still in development, so the way to prevent the spread of Covid-19 is done by changing people's behavior. This study aims to determine the effect of risk perception, optimism bias, and personality on the Covid-19 transmission preventive behaviors in the form of washing hands, maintaining physical distance, and wearing masks. The study used a survey method that asked participants to fill out an online questionnaire. A total of 271 people participated as respondents in this study. The results of multiple linear regression analysis indicate that risk perceptions have a positive effect on the behavior of washing hands, maintaining physical distance, and using masks. Conscientiousness personality has positive effects on the habits of washing hands and physical distancing but does not affect the habit of wearing masks. Contrary to the hypothesis, the optimism bias has positive effects on handwashing and physical distancing habits but does not affect the habit of wearing masks.